Pengembangan Sistem Management Dalam Melakukan Penugasan Berbasis Web - Bobby Ardian Ekaputra; Fajar Pradana; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Understanding the importance of control over various aspects of conducting an assignment in completing a goal, good management is needed so that the assignment can run as expected. Management is needed as a principle to do every planning, there are several factors that make management must be done in the assignment. Completion of various assignments that require generalization so that workmanship can be well organized. In addition, control in terms of time, priority, and minor assignments becomes a necessity in management so that the assignment work can be in line with expectations. Projects can be used as applications in doing assignments due to collaborative work and planning involvement in achieving a goal. The management system is expected to be a place and facility to help the management of assignments to be better from the beginning of the process until the end. The system will be built based on a website so that it can be accessed through hardware such as laptops or smartphones. The results of the research using a questionnaire are divided into users who have not and already know a team-collaboration based system, from the responses received and calculated using the System Usability Scale (SUS) method, it is found that users who do not know the team-collaboration based system get average an average score of 65 and users who already know a team-collaboration-based system get an average value of 74.2.